The impact of cognitive fitness and gender on sleep quantity and timing and mental health of competitive athletes - Mascaro, L.; Drummond, S.; Leota, J.; Boardman, J.; Hoffman, D.; Rajaratnam, S.; Aidman, E.; Facer-Childs, E. (SLEEP Advances, 2021)
Introduction: Mental fitness is increasingly considered key to an athlete`s competitive arsenal. Its active ingredients include cognitive fitness factors, such as impulse control, and recovery factors, such as sleep, which may differ between male and female athletes. Our study investigated: 1) gender differences in cognitive fitness; and 2) the associations of gender and cognitive fitness with sleep and mental health in competitive athletes during the COVID-19 lockdown. Methods: 84 athletes competing at levels from regional/state to international (42F, mean age=23.2) completed a questionnaire battery containing validated measures of: a) depression, anxiety, and stress; b) sleep (Total Sleep Time, Sleep Latency, mid-sleep time on training- and competition-free days); and c) self-control, intolerance of uncertainty, and impulsivity (representing cognitive fitness constructs). Results: Female athletes reported significantly higher depression, anxiety, and stress, a later mid-sleep time on free days, lower self-control, higher intolerance of uncertainty, and higher positive urgency impulsivity compared with male athletes. Self-control was negatively associated, and intolerance of uncertainty was positively associated, with depression, anxiety, and mid-sleep time on free days. Discussion: Female athletes in our sample reported poorer mental health and cognitive fitness, and later sleeping times on free days. Greater cognitive fitness was associated with better mental health, independent of gender. Overall, these findings are consistent with prior work in community samples. Future work should examine the source(s) of these gender differences. If replicated, our findings would suggest a need to develop interventions aimed at improving athlete well-being, potentially with a particular focus on female athletes.